2000
DOI: 10.1080/00914030008054868
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Behavior of Mica-Polystyrene Composite

Abstract: The electrical properties of mica-polystyrene composites were studied using the impedance measurements technique. The study was carried out as a function of frequency and mica concentration. It was observed that the AC conductivity and the dielectric constant are increased with increasing of the mica content in the composite. The observed electrical results fit approximately the reported empirical equations concerning the AC conductivity and dielectric behavior of polymer composites. Relaxation processes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…The high impedance values at low frequencies, which mean more resistive behavior, are due to electrode and space charge polarization. The space charge polarization (or Maxwell-Wagner) resulted from some structural defects such as cluster phases, grain boundaries, and accumulations carrying unbound charges at the interfaces [4,10]. In general, the rapid decrease of impedance values with frequency indicates a response with the alternating electric field and may be attributed to the reduction of the interfacial polarization effect, which may exist in the electrode-specimen surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high impedance values at low frequencies, which mean more resistive behavior, are due to electrode and space charge polarization. The space charge polarization (or Maxwell-Wagner) resulted from some structural defects such as cluster phases, grain boundaries, and accumulations carrying unbound charges at the interfaces [4,10]. In general, the rapid decrease of impedance values with frequency indicates a response with the alternating electric field and may be attributed to the reduction of the interfacial polarization effect, which may exist in the electrode-specimen surface.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of mineral fillers, including clays and zeolites, to polymeric matrices can improve the electrical and dielectric properties of insulating polymers [3][4][5][6][7]. Kaolinite is a clay mineral with chemical composition Al 2 (Si 2 O 5 )(OH) 4 and layered silicate structure linked through oxygen atoms to one octahedral sheet of alumina octahedral represented by Al 2 ðOHÞ þ2 4 . The kaolinite grains are found in the form of plates throughout the sedimentary rocks of volcanic origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high values of " 0 at low frequency are due to space charge polarization (Wagner-Maxwell effect). 13,14,16 The dielectric constant values of the composites are higher than that of pure PS due to metallic impurities oxides existing in the oil shale mineral. 15,16 The dependence of dielectric constant (" 0 ) and dielectric loss (" 00 ) on temperature are shown in Figures 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…AbuHijleh et al observed that ac conductivity and dielectric constant increase with increase of mica content in composite [17]. The objective of this research is to study the dielectric properties with annealing effect.…”
Section: Introductionmentioning
confidence: 99%